Reviewing the Human Capital Performance Stimulants of Employees In Logistic Transportation with a Quantitative Approach - Alkistasari, Intan; Harianto, Eric (Universitas Ciputra Surabaya, 2022)
This study aims to determine the effect of work discipline, work environment, andorganizational culture on job satisfaction and employee performance in logisticstransportation companies. This study uses a sampling technique that is saturated sample.The population used in this study were all employees of PT. Surya Lintas Abadi, totaling56 people. This research was conducted from May 2021 to December 2021. This researchmethod is quantitative with data collection using questionnaires. The analytical methodused is Partial Least Square (PLS). The results of this study are work discipline has aneffect on job satisfaction, work environment has an effect on job satisfaction, organizationalculture has an effect on job satisfaction, job satisfaction has an effect on employeeperformance, work discipline has no effect on employee performance, work environmenthas an effect on employee performance, organizational culture has an effect on employeeperformance. Of the seven existing hypotheses, the biggest influence is the effect of workdiscipline on job satisfaction.PT. Surya Lintas Abadi can increase employee satisfactionby making employees have time discipline. The hypothesis that has no effect is the effect ofwork discipline on employee performance .PT. Surya Lintas Abadi needs to implement akey performance index as a tool to make it easier to assess and evaluate employeeperformance.